2017
DOI: 10.1093/mnras/stx168
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of four ‘hypervariable’ AGN: a micro-needle in the haystack?

Abstract: We analyse four extreme active galactic nuclei (AGN) transients to explore the possibility that they are caused by rare, high-amplitude microlensing events. These previously unknown type-I AGN are located in the redshift range 0.6-1.1 and show changes of > 1.5 mag in the g band on a time-scale of ∼years. Multi-epoch optical spectroscopy, from the William Herschel Telescope, shows clear differential variability in the broad line fluxes with respect to the continuum changes and also evolution in the line profile… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 55 publications
0
11
1
Order By: Relevance
“…This result suggests that at least some part of broad Mg ii reverberates to continuum changes, or that the continuum flux that ionizes broad Mg ii varies less than the continuum at rest-frame 3000Å. It is interesting to note that Bruce et al (2017) found that Mg ii flux does not seem to respond to continuum variations in two extreme variability quasars, where the extreme variability can be caused by rare, high-amplitude microlensing events.…”
Section: Mg II Line Variationmentioning
confidence: 96%
“…This result suggests that at least some part of broad Mg ii reverberates to continuum changes, or that the continuum flux that ionizes broad Mg ii varies less than the continuum at rest-frame 3000Å. It is interesting to note that Bruce et al (2017) found that Mg ii flux does not seem to respond to continuum variations in two extreme variability quasars, where the extreme variability can be caused by rare, high-amplitude microlensing events.…”
Section: Mg II Line Variationmentioning
confidence: 96%
“…The data reduction was performed with a pipeline using custom pyraf scripts and standard techniques. The pipeline is described in detail in Bruce et al (2017) (Section 2.3.3 in that paper).…”
Section: William Herschel Telescope Optical Spectroscopic Monitoringmentioning
confidence: 99%
“…Other, rarer events, such as stellar tidal disruption, supernovae in the nuclear regions, and gravitational microlensing, have also been proposed (e.g. Lawrence et al 2016, Bruce et al 2017 and references therein). To make further progress it is important to better characterise the properties of variability to help distinguish between the various mechanisms responsible.…”
Section: Introductionmentioning
confidence: 99%
“…With the light curve noted in the previous section, we take a similar approach to modelling the lensing event as Bruce et al (2017). Our first assumption is that the event can be well described by a simple microlensing model of a pointmass object passing in front of a background point-source.…”
Section: Microlensing Analysismentioning
confidence: 99%
“…In this paper, we wish to re-examine the microlensing hypothesis. Recent observations have suggested that a number of long-lived AGN transients can be explained as the result of isolated microlensing events Bruce et al 2017). Not only does this remain a viable explanation for the Sharov21 event, it may also be the tip of the proverbial iceberg for the archival/future detection of microlensed background AGN in the vicinity of M31 or other nearby galaxies.…”
Section: Introductionmentioning
confidence: 99%